1995
DOI: 10.1093/carcin/16.10.2331
|View full text |Cite
|
Sign up to set email alerts
|

Risk of smoking for squamous and small cell carcinomas of the lung modulated by combinations of CYP1A1 and GSTM1 gene polymorphisms in a Japanese population

Abstract: Genes for cytochrome P4501A1 (CYP1A1) and glutathione S-transferase class mu (GSTM1) have been shown to be polymorphic, and have been implicated in tobacco-related carcinogenesis. In the present study, the role of the combined genotypes CYP1A1 and GSTM1 as a possible modulator of smoking related lung cancers was studied in relation to the tobacco smoke exposure level in 118 Japanese patients aged < 70 with squamous or small cell carcinomas of the lung. Among male smoking patients, the overall proportion of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(61 citation statements)
references
References 0 publications
4
55
1
1
Order By: Relevance
“…Since CYP1A1 is involved in the activation of procarcinogens, it is reasonable to observe an association between CYP1A1 polymorphism and cancer risk, especially in cancers caused by chemical carcinogens. For example, it has frequently been reported that an increased risk of lung cancer is related to variant CYP1A1 Msp1 genotypes (Kawajiri et al, 1993;Kihara and Noda, 1995;Xu et al, 1996); however, the results vary among ethnic groups (Drakoulis et al, 1994;Hirvonen et al, 1992;Alexandrie et al, 1994). In breast cancer, a significant association related to Msp1 polymorphism was found in African-American patients (Taioli et al, 1995); however, this was not apparent in Caucasians (Bailey et al, 1998;Ishibe et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Since CYP1A1 is involved in the activation of procarcinogens, it is reasonable to observe an association between CYP1A1 polymorphism and cancer risk, especially in cancers caused by chemical carcinogens. For example, it has frequently been reported that an increased risk of lung cancer is related to variant CYP1A1 Msp1 genotypes (Kawajiri et al, 1993;Kihara and Noda, 1995;Xu et al, 1996); however, the results vary among ethnic groups (Drakoulis et al, 1994;Hirvonen et al, 1992;Alexandrie et al, 1994). In breast cancer, a significant association related to Msp1 polymorphism was found in African-American patients (Taioli et al, 1995); however, this was not apparent in Caucasians (Bailey et al, 1998;Ishibe et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Phase II enzymes can detoxify and process the activated metabolites for final breakdown or excretion. Therefore, the genotypes with high phase I enzyme activity and low phase II enzyme level are considered to pose a high risk of cancer development [2] . Cytochrome P450 (CYP) isoenzymes are one major kind of phase I enzymes and play an important role in the oxidation of chemical compounds, such as polycyclic aromatic hydrocarbons (PAH), often resulting in the formation of highly reactive compounds that are the ultimate carcinogens [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the association between CYP1A1 polymorphisms and breast cancer risk. For the CYP1A1 polymorphism the reports are also inconclusive; one study reports a decrease in breast cancer risk in Japanese women associated with the CYP1A1 (11). Seven studies examined, individually, the frequencies of both GSTM1 and GSTT1 null genotypes in cases and controls.…”
Section: Resultsmentioning
confidence: 99%
“…All patients and controls were of turkish population. Genotyping assays CYP1A1 genetic polymorphisms were determined as previously described (8,9,11,14). Primer pair sets were used to detect the polymorphism within exon 7 of the CYP1A1 gene by PCR where the praimer set consisted of sense primer 1A1A: 5'-GAAGTGTATCGGTGAGACCA-3' and antisense primer c53: 5'-GTAGACAGAGTCTAGGCCTCA-3', located about 190 bp downstream of the polymorphism site (Fig.…”
Section: Patients and Dna Isolationmentioning
confidence: 99%